EMERGENCY VEHICLE ROUTING PROBLEM FOR POST-DISASTER MANAGEMENT - Mahmat, Zeliha; Sua, Lutfu S.; Balo, Figen (American Institute of Physics Inc., 2021)
[Abstract Not Available]
Keywords: Civil defense; Disasters; Emergency vehicles; Post-disaster management; Vehicle Routing Problems; Disaster prevention